The Influence of Celebrity Endorsers On Social Media On Tourists' Visiting Interest In Melasti Beach Bali - Putri , Ni Nyoman Elsa Cahyani Ariani; Dianasari, Dewa Ayu Made Lily; Subrata, I Made (Journal of Applied Science in Tourism Destination, 2023)
One of the efforts to increase interest in visiting is to design various marketing and tourism strategies, one of which is the endorser strategy. This research aims to determine the effect of celebrity endorsers in social media on the interest of visiting tourists at Melasti Beach. This research belongs to the type of quantitative research. The population in this study is domestic millennial tourists who visit the Melasti Beach tourist attraction with a sample of 200 respondents. This research data collection uses a questionnaire distributed online with the help of a barcode containing a google form and analyzed using SEM with SmartPLS 3.0 software. The results of this analysis indicate that the effectiveness of the Celebrity endorser with the highest average value of 4.28% and the lowest average value of 3.84%, the celebrity endorser has a significant effect on visiting interest, social media with the highest average value of 4 .29% and the lowest average value is 3.36%, then social media has a significant effect on visiting interest, social media with the highest average value is 4.19% and the lowest average value is 3.83% so it has a significant effect on interest in visiting and social media are able to mediate the influence of celebrity endorsers on visiting interest.